Evaluation of the Implementation Senayan Library Management System (SLiMS) at SMAN 8 Mandau and SMAS Cendana Libraries in Mandau District - Herlia Septina; Meilina Bustari (FKIP - Universitas Riau, 2026)
The main problem identified in school libraries in Indonesia, particularly in Mandau regency, is the continued use of manual management systems. Manual processes in cataloging, circulation, and member management lead to significant administrative inefficiencies such as slow service delivery, high risk of human error, and inaccurate data reporting. This study aims to evaluate the implementation on one of library automation system, such as the Senayan Library Management System (SLiMS) application at the Library of SMAN 8 Mandau and the Library of SMAS Cendana Mandau in Mandau regency. This study focuses on evaluating three main aspects, human resources (brainware), hardware, and software in the implementation of SLiMS in library services. This study employed a qualitative method, and data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The research informants consisted of school principals, library heads, library staff, and library users at both schools. The results of the study indicate various maturation level (from poor to very Good) at two pioneering school operating SliMS application in Mandau Regency, Riau. The study established required criteria and challenge that need to be met by other school that wish to implement SliMS.